Barriers in the implementation of interprofessional continuing education programs – a qualitative study from Germany - Altin, Sibel V (BMC Med Educ, 2014)
BACKGROUND: Insufficient communication and coordination is one of the most problematic issues in German health care delivery leading to detrimental effects on health care outcomes. As a consequence interprofessional continuing education (CIPE) is gathering momentum in German health policy and health care practice aiming to enhance service quality and patient safety. Nevertheless, there is limited evidence on the course of implementation and the perceived effectiveness/acceptance of CIPE in German health care. This paper describes the objectives and formal characteristics of CIPE trainings and maps important determinants influencing the success of CIPE implementation from the perspective of providers offering CIPE trainings for German health care professionals. METHODS: Forty-nine training institutions offering CIPE for health care professionals were identified by a structured web search including the websites of German medical education associations and public/private training institutions. Directors and managers of the identified institutions were invited to participate in a semi-structured interview. The interview guideline was developed using the SPSS method by Helferich and colleges. Interviews were analyzed using the summarizing content analysis developed by Mayring resulting in a paradigm that contextualizes hindering factors regarding the implementation of CIPE in the German health care system. RESULTS: Overall, 19 of the identified institutions agreed to participate with one director/manager per institution resulting in a response rate of almost 38.8%. The included institutions offer n = 85 CIPE trainings for health care professionals. Trainings offered mainly address the enhancement of domain, social and personal competencies of the participating health care professionals and follow three main objectives comprising better care of severely ill patients, improvement of patient safety by sustained risk management as well as a more patient centered care. Implementation of CIPE in Germany is influenced by various hindering factors mostly coming from systemic (missing incentives), behavioral (hierarchy problems) and methodological (limited quality assurance) factors. CONCLUSION: CIPE is an evolving concept in the German health care system. There are various difficulties that impede a successful implementation of CIPE and might be mitigated by specific health policy interventions such as mandatory CIPE participation of health care professionals and comprehensive pre-license interprofessional education. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1472-6920-14-227) contains supplementary material, which is available to authorized users.